Nonuniform behavior and stability of Hopfield neural networks with delay - Bento, António J. G (2017)
Based on a new abstract result on the behavior of nonautonomous delayed equations, we obtain a stability result for the solutions of a general discrete nonautonomous Hopfield neural network model with delay. As an application we improve some existing results on the stability of Hopfield models.